2018
DOI: 10.1073/pnas.1804735115
|View full text |Cite
|
Sign up to set email alerts
|

NT3-chitosan enables de novo regeneration and functional recovery in monkeys after spinal cord injury

Abstract: Spinal cord injury (SCI) often leads to permanent loss of motor, sensory, and autonomic functions. We have previously shown that neurotrophin3 (NT3)-loaded chitosan biodegradable material allowed for prolonged slow release of NT3 for 14 weeks under physiological conditions. Here we report that NT3-loaded chitosan, when inserted into a 1-cm gap of hemisectioned and excised adult rhesus monkey thoracic spinal cord, elicited robust axonal regeneration. Labeling of cortical motor neurons indicated motor axons in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
108
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 47 publications
1
108
0
1
Order By: Relevance
“…The chitosan-collagen carrier was chosen based on well-characterized properties of tunable structural stability, excellent biocompatibility, low antigenicity, and high biodegradability [43,58,59]. Other researchers have already demonstrated that chitosan-collagen carriers can deliver therapeutic agents to the spinal cord [21,41]. In prior work neurotrophin-3 (NT3), a neurotrophic growth factor that promotes proliferation of neural stem cells, enhanced functional recovery after SCI in rats when delivered by chitosan-collagen carriers [21,41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chitosan-collagen carrier was chosen based on well-characterized properties of tunable structural stability, excellent biocompatibility, low antigenicity, and high biodegradability [43,58,59]. Other researchers have already demonstrated that chitosan-collagen carriers can deliver therapeutic agents to the spinal cord [21,41]. In prior work neurotrophin-3 (NT3), a neurotrophic growth factor that promotes proliferation of neural stem cells, enhanced functional recovery after SCI in rats when delivered by chitosan-collagen carriers [21,41].…”
Section: Discussionmentioning
confidence: 99%
“…Many minimally invasive and regenerative therapeutics are under investigation ranging from regenerative therapy with hydrogel implants, stem cells, growth factors, magnesium and antioxidants, among others, but without proven long term benefits at this time [1,2,[4][5][6][7][11][12][13]17,18]. Chitosan hydrogels with or without growth factors have been proven to promote SCI restoration and axon regeneration in rat and monkey models [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have achieved favorable effect in rodent models, so preclinical studies have further expanded to non-human primates (NHPs). 7 SCI repair studies of NHP usually require the use of an in vivo longitudinal examination technique because a long time period is needed for spinal cord tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed surgical procedures were executed as described in previous studies. 7,34 Briefly, spinal cord tissue injury was performed after laminectomy under an operation microscope. A tissue mass with 5 mm length (in the superioinferior direction) and 2-3 mm width (in the left-right direction) was excised by using microscissors.…”
Section: Introductionmentioning
confidence: 99%